ENTREPRENEURSHIP AS A STEP TOWARDS PROFESSIONAL GROWTH OF A VOCATIONAL SCHOOL GRADUATE (Innovative professional education, 2025)
This article examines the role of entrepreneurship as an important step toward to the professional growth of graduates of vocational (vocational-technical) educational institutions (VET). It was investigated that the modern challenges of labor market include the necessity of the development of entrepreneurial skills among young professionals. Key competencies were identified, that contribute to a successful business start or effective employment. Special attention is given to the formation of an entrepreneurial mindset during the educational process, methods of supporting young entrepreneurs, and the prospects for small business development among VET graduates
Keywords: entrepreneurship, professional growth, graduate, VET, competencies, labor market, business